The Effect of Good Corporate Governance and Financial Performance on Company Value - Ray Farandy Suhardi; Jul Aidil Fadli (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
This study aims to determine and analyze the effect of good corporate governance and financial performance on firm value. The population used in this study are manufacturing companies in the food and beverage sector which are listed on the Indonesian stock exchange in 2015-2019. The sample in this study was selected using purposive sampling method with predetermined criteria in order to obtain as many as 10 samples. The analytical method used is descriptive statistical test analysis and hypothesis testing using multiple linear regression analysis. The results of the study show that good corporate governance and financial performance together have an influence on firm value. The results of the partial test showed that there was no effect between the number of independent commissioners on firm value, while the number of female board of directors and financial performance had an effect on firm value.